Effect of Oral Nirmatrelvir on Long COVID Symptoms: 4 Cases and Rationale for Systematic Studies - Michael Peluso; Khamal Anglin; Matthew S. Durstenfeld; Jeffrey N. Martin; J. Daniel Kelly; Priscilla Y. Hsue; Timothy J. Henrich; Steven G. Deeks (Pathogens and Immunity, 2022)
Background: Efforts to understand the impact of SARS-CoV-2 variants, vaccine status, and treatment on the development and persistence of Long COVID have intensified.